Cultivar diversity in nordic spring barley breeding (1930-1991) - Ortíz, R.; Nurminiemi, M.; Madsen, S.; Rognli, O.; Bjornstad, A. (Springer, 2002)
A phenotypic diversity index (PDI) was calculated using 10 agronomic characteristics recorded in 90 accessions of 2-row spring barleys and 29accessions of 6-row spring barleys grown in the Nordic Region. The PDI ranged from 0.0308 to 0.6245 in 2-row barley accessions and from0.0314 to 0.7016 in 6-row barley accessions. The average PDIs were0.2178 and 0.2438 in 2-row and 6-row barley germplasm, which confirms that some older cultivars were parents of newer cultivars. The lowest PDI was between accessions with the same name, which suggest that irrespective of their market source, they were the same cultivars. The largest PDI ranges in 2-row barley cultivars within the same country or release decade were correlated to the number of accessions in the respective cluster, which suggests that phenotypic diversity in this germplasm depends on the number of cultivars included in the cluster. However, this association was not always observed in 6-row barley cultivars. The most distinct 2-row cultivars were Arla and Akka from Sweden, whereas Sigur and Tampa from Iceland were the most distinct 6-row cultivars as determined by both PDI and average linkage cluster analysis. This analysis also confirm that the 2-row barley accessions Jenny, Triumph, and Vega, which were obtained from two distinct market sources, and the 6-row barley accessions under the name Agneta (but from three market sources) were the same. The analysis of variance of the PDI indicates that 6-row germplasm may be clustered according to their geographical origin or decade of release, but this was not observed in 2-row barley germplasm. This research demonstrates the advantage of PDI to assess variation among breeding pools.